2015
DOI: 10.1021/acs.jpclett.5b00002
|View full text |Cite
|
Sign up to set email alerts
|

VUV Photoelectron Spectroscopy of Cysteine Aqueous Aerosols: A Microscopic View of Its Nucleophilicity at Varying pH Conditions

Abstract: Cysteine (Cys) is unique due to its highly reactive thiol group. It often regulates the biological function of proteins by acting as the redox site. Despite its biological significance, however, the valence electronic structure of Cys under the aqueous environments remains unavailable. Here, we report the VUV photoelectron spectroscopy of Cys aqueous aerosols via a newly built aerosol VUV photoelectron spectroscopy apparatus. The photoelectron spectra of Cys show distinct band shapes at varying pH conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 59 publications
(102 reference statements)
0
47
0
Order By: Relevance
“…148151 Cys often serves as the redox active site in peptides and proteins. Recently, Su et al 152 reported the valence electronic properties and pH-dependent ionization energies of Cys aqueous bioaerosols using the aerosol VUV photoelectron spectroscopy. Ionization energy determines how readily the electron can be taken away from the donor.…”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…148151 Cys often serves as the redox active site in peptides and proteins. Recently, Su et al 152 reported the valence electronic properties and pH-dependent ionization energies of Cys aqueous bioaerosols using the aerosol VUV photoelectron spectroscopy. Ionization energy determines how readily the electron can be taken away from the donor.…”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%
“…Their results show altered molecular orbital character of Cys when its form changes with pH. 152 Deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) are also prone to the oxidizing potential of ozone. 145,153,154 …”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%
“…Aerosol photoelectron spectroscopy has become an important method for studying the electronic structure of isolated submicrometer particles, free from the influence of substrate or solvent. , This technique is based on the interaction of focused particle beam with vacuum-ultraviolet (VUV)/soft X-ray radiation under high-vacuum conditions. The photoelectrons formed in this interaction can be subsequently detected or discriminated according to their kinetic energies and/or momenta. Different systems have been investigated so far, such as aerosols produced from aqueous solutions of salts and organic molecules, , or gas-phase noble-metal nanoparticles produced by heating metal wires. , Recently, attention has been focused on photoemission spectroscopy studies of the aerosols obtained by dispersion of nanoparticle colloids including SiO 2 , , TiO 2 , , carbon dots, quantum dots, , and Titan analogue aerosols (Tholins) . The main advantage of this approach is that isolated nanosystems can be directly produced from respective colloids without the need for additional preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol photoelectron spectroscopy is an important tool for the study and characterization of the electronic structure of particulate matter, elucidating properties specific to submicrometer sized particles, often governed by surface effects. Furthermore, aerosol photoelectron spectroscopy can be used as an alternative and often advantageous approach to obtain information on solid and liquid bulk properties, such as bulk ionization energies, , solvation effects, and electron transport phenomena. …”
mentioning
confidence: 99%